Tehnološko modeliranje energetskih procesov: Zbirka rešenih vaj - Igrec, Dalibor (University of Maribor Press, 2022)
Technological Modelling of Power Processes: Collection of Solved Exercises. The collection of solved exercises represents additional teaching material with solved tasks in the subject Technological modelling of power processes, which is intended primarily for master’s students at the Faculty of Energy, University of Maribor. The material includes three key chapters that need to be understood and solved independently within the course. The first chapter presents the simplification of block diagrams, where with the help of the rules of algebra, the process of simplification by individual steps is shown on examples. The second chapter includes a presentation of a block diagram from a differential equation, where the conversion to a block diagram from the corresponding differential equation is shown. The last chapter covers methods for numerical solving of differential equations, where in the case of a differential equation under a given initial condition, the calculation is postponed with the whole procedure by analytical and Euler method and Runge Kutta method of 2nd and 4th order.